Meningkatkan Kemampuan Mengenal Huruf Melalui Permainan Mencari Jejak (Maze) Pada Anak Kelompok B - Nengsi, Kiki Julia; Haryono, Mimpira; Sari, Rika Partika (UNIVED Press, Universitas Dehasen Bengkulu, 2022)
The purpose of this study was to find out whether tracing games could improve the ability to recognize letters in group B in the MELATI INDAH PAUD Unit, Padang Kelapo Village, Semidang Alas Maras District, Seluma Regency. Classroom Action Research (PTK) which is focused on classroom situations, or commonly known as classroom action research, the procedure used is in the form of a cycle. The main subjects in this study were in group B totaling 16 people. This Classroom Action Research uses the John Elliot model where each cycle consists of four main activities, namely planning, implementing, observing, and reflecting which are carried out through two cycles, namely cycles I and II, each cycle consisting of one meeting. Data collection techniques using observation and documentation methods. Data analysis was carried out in a qualitative-quantitative descriptive manner with the emphasis being used to determine process improvements expressed in a predicate, while quantitative data analysis was used to determine yield improvements using percentages. The results of increasing the ability to recognize letters through games to find traces in group B at PAUD MELATI INDAH in cycle I meeting I was 74% and in cycle II meeting I was found to be an increase of 87.75%. The conclusion of the research that through the game to find traces can improve children's ability to recognize letters, it is proven that in cycle II there was a significant increase, the percentage of achievement was 87.75% with very good development criteria (BSB).